Analysis of Factors Influencing Poverty Levels and Their Influence on GRDP Growth in 11 Provinces in Indonesia - Rahmat Pujiyanto; Heru Subiyantoro (Return : Study of Management, Economic and Bussines, 2026)
Poverty remains a persistent development challenge in Indonesia, with significant regional disparities, particularly across the 11 provinces of Sumatra Island, where poverty rates vary widely and are often not proportional to economic growth. This research analyzes factors influencing the poverty rate and its effect on Gross Regional Domestic Product (GRDP) growth in 11 provinces of Sumatra Island from 2015 to 2022. Variables include open unemployment rate, average years of schooling, regional government expenditure, and investment realization. The analytical method was panel data with a fixed effect model (FEM) using EViews 12 software. Results show that unemployment positively and significantly affects poverty, while education, government expenditure, and investment have negative and significant effects. Furthermore, poverty negatively and significantly affects GRDP growth. These findings indicate that reducing poverty through improved education and accelerated investment realization can meaningfully stimulate regional economic growth. In conclusion, reducing poverty through improved education and accelerated investment realization can meaningfully stimulate regional economic growth, and poverty alleviation must be integrated as a core strategy in regional development planning.